Patriarchal bias against nature and women in “The Red Bekisar” by Ahmad Tohari: an ecofeminist reading - Carina Fernanditha (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
Ahmad Tohari is one of the most famous Indonesian contemporary novelists, whose works are praised for their social and environmental criticism. The Red Bekisar is one of Tohari’s stories which specifically focuses on the danger of metropolitan life compared to the wisdom of the traditional way of living close to nature and God. With a woman as the lead character, The Red Bekisar might pass as a literary work representing environmental and feminist values at first glance. However, this research argues that when analyzed from the framework of ecofeminism, especially concerning the symbolic connection between nature and women, The Red Bekisar uses languages that naturalize women and feminize nature. It presents nature and women according to the patriarchal bias; as "others" who are wild, alluring to be conquered, dependent on male caretakers, and ultimately, as less than men.